The cicada genus Karenia Distant, 1888 (Hemiptera: Cicadidae), with description of a new species - Pham, Hong-Thai; Constant, Jerome (Zootaxa, 2014)
The cicadas of the genus Karenia are reviewed, and Karenia tibetensis sp.nov. (Hemiptera: Cicadidae) is described from Tibet, China. Pictures of the male adult and illustrations of the male genitalia are provided. A key to the species of Karenia is presented and the distribution of the Karenia species is discussed